2015
DOI: 10.1371/journal.pone.0128897
|View full text |Cite
|
Sign up to set email alerts
|

The VEGF-Receptor Inhibitor Axitinib Impairs Dendritic Cell Phenotype and Function

Abstract: Inhibitors of VEGF receptor (VEGFR) signaling such as sorafenib and sunitinib that are currently used in the treatment of malignant diseases have been shown to affect immunological responses by inhibition of the function of antigen presenting cells and T lymphocytes. The VEGFR-inhibitor axitinib has recently been approved for second line therapy of metastatic renal cell carcinoma. While there is some evidence that axitinib might interfere with the activation of T cells, not much is known about the effects of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 21 publications
4
23
0
Order By: Relevance
“…A genetic variant in VEGFA was here associated with increased circulating VEGF and shown to have a causal cascade effect on IL7, IL10, IL13 and IL12p70 (Fig 2C-D). Axitinib, a VEGF-receptor inhibitor, has been shown to reduce IL12p70 production in cultured monocyte-derived dendritic cells 29 , which support our findings. Furthermore, VEGFA-transcription follows the same temporal pattern with IL7 transcription during wound healing, and it has been suggested that the secretion of these two cytokines might be connected by the same pathway 30 .…”
Section: Discussionsupporting
confidence: 91%
“…A genetic variant in VEGFA was here associated with increased circulating VEGF and shown to have a causal cascade effect on IL7, IL10, IL13 and IL12p70 (Fig 2C-D). Axitinib, a VEGF-receptor inhibitor, has been shown to reduce IL12p70 production in cultured monocyte-derived dendritic cells 29 , which support our findings. Furthermore, VEGFA-transcription follows the same temporal pattern with IL7 transcription during wound healing, and it has been suggested that the secretion of these two cytokines might be connected by the same pathway 30 .…”
Section: Discussionsupporting
confidence: 91%
“…2D). We used the tyrosine kinase inhibitor axitinib, which blocks VEGF receptor signaling (35), and bevacizumab, an anti-VEGF neutralizing antibody (36), to mechanistically link circulating VEGF and Jagged1 induction. Both axitinib and bevacizumab inhibited Jagged1 induction in ECs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, inhibition of VEGF-signaling during DC maturation in vitro or by treating tumor-bearing mice with sunitinib in vivo has previously been demonstrated to inhibit DC activation [20, 21]. Therefore, we investigated if combining anti-CD40 mAb therapy with sunitinib treatment affects the activation status of conventional DCs (cDCs) (B220 − CD11b +/− CD11c + ) in the tumor draining lymph node.…”
Section: Resultsmentioning
confidence: 99%
“…While the main antitumor effects of agonistic anti-CD40 antibodies are through activation of DCs, sunitinib has been shown to decrease DC activation [20, 21]. However, CD40-induced DC activation was not hampered by co-treatment with sunitinib in neither the B16.F10 melanoma model nor the T241 fibrosarcoma model (Figure 2A-2B).…”
Section: Discussionmentioning
confidence: 99%